Transthoracic echocardiography‐guided left bundle branch pacing without fluoroscopic guidance: A case report. Issue 1 (31st March 2020) - Tan, Kunyue; Deng, Xiaoqi; Wang, Shuzhen; Liu, Chunxia; Zhao, Ruohan; Xiong, Feng
Abstract: This case study demonstrates the feasibility of pacing the left bundle branch and atrial septum under transthoracic echocardiography (TTE) without fluoroscopic guidance. This technique could be useful to guide pacemaker implantation in some patients, especially pregnant women.